Research progress of fungi and their functional properties in the brewing process of sauce-, strong- and light-flavor Baijiu - HAN Bingyu, CHEN Huitai, LI Zongjun (Zhongguo niangzao)
Fungi exist in Baijiu Daqu and the whole brewing process of Baijiu, which is vital to the flavor and quality of Baijiu. The fungi in Baijiu brewing are mainly yeasts and molds. Molds can produce a variety of enzymes that decompose macromolecular substances such as protein and starch, which provide fermentation power and enzyme power for Daqu production and Baijiu brewing. Some metabolites of molds also have important effects on the quality of base liquor and the flavor of Baijiu. Yeast has the functional characteristics of producing ethanol, ester and a variety of flavor metabolites. In this paper, three basic flavor types (sauce-flavor, strong-flavor and light-flavor) Baijiu were introduced, the community structure diversity of the dominant yeasts and molds in the brewing process of sauce-, strong- and light-flavor Baijiu were mainly described, and the functional characteristics of yeasts and molds were summarized, aiming to provide reference for the analysis and use of functional fungi in the brewing process of Baijiu, as well as the improvement of the flavor and quality of Baijiu.